1984
DOI: 10.1097/00000658-198411000-00003
|View full text |Cite
|
Sign up to set email alerts
|

The Bacteriology and Septic Complication of Patients with Appendicitis

Abstract: A detailed bacteriologic study was done on 161 patients operated for appendicitis. Aerobic and anaerobic cultures were taken from the blood, the appendicular lumen, mucosa, serosa, fossa, and from the wound after closure of the peritoneum. There is no correlation between the degree of appendicitis and the incidence of positive blood culture. The infection spread through the appendicular wall as the disease progressed. Aerobic infection was common in early appendicitis but a mixed aerobic and anaerobic infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
2

Year Published

1986
1986
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 16 publications
1
35
0
2
Order By: Relevance
“…Its effectiveness against some aerobic and anaerobic bacteria has been also shown by hers. 23 Addition of topical antibiotics to systemic antibiotics was found beneficial in advanced appendicitis. [24][25] Bergamini et al 11 demonstrated in an experimental study that when wound contamination is great, a combination of topical and systemic antibiotics becomes more effective.…”
Section: Discussionmentioning
confidence: 99%
“…Its effectiveness against some aerobic and anaerobic bacteria has been also shown by hers. 23 Addition of topical antibiotics to systemic antibiotics was found beneficial in advanced appendicitis. [24][25] Bergamini et al 11 demonstrated in an experimental study that when wound contamination is great, a combination of topical and systemic antibiotics becomes more effective.…”
Section: Discussionmentioning
confidence: 99%
“…Elevation in serum CRP levels is seen with most invasive infections, grampositive and gram-negative bacterial systemic infections cause marked CRP rises, even in immunodefi cient patients [34], CRP has also been identifi ed as a marker of infection in patients with SIRS [35]. As a consequence, the increased levels shown by CRP in advanced perforated appendicitis are easily explained; patients with perforated appendicitis have a systemic infection caused by gram-negative bacteria, mainly Escherichia coli [22,23], these patients often have a SIRS, consequently their CRP levels rise progressively along with the time of evolution of appendicitis, from the onset to diagnosis and treatment.…”
Section: Laboratory Tests: Wbc and Crpmentioning
confidence: 99%
“…Recently, it has been proposed that an elevated total bilirubin (TB) level could be used as a specifi c marker for the prediction of perforated appendicitis [19,20]. The rationale for this proposal is based on the hepatic dysfunction occurring during bacterial sepsis secondary to Gram negative bacteria [21], such as Escherichia coli, which is the main bacteria present in patients with appendicitis [22,23]. Consequently a low-grade hyperbilirubinaemia, often unnoticed in septic patients not presenting clinically evident jaundice, is present in patients with gram-negative infections [24].…”
Section: Introductionmentioning
confidence: 99%
“…The risk of postappendectomy infections is related to the stage of appendicitis and varies from less than 10% following removal of a normal appendix to more than 50% in perforated appendicitis [1][2][3][4]. Systemic antibiot ics given pre-or intraoperatively effectively decrease the risk of wound infection and intraperitoneal sepsis [5][6][7][8][9][10], Controversy still exists, however, as to type of anti biotics, route of administration and duration of treat ment [1,11], Patients with gangrenous appendicitis are at high risk of developing postsurgical infection [12][13][14] and results from controlled studies support the benefit of antibiotic therapy in addition to surgery even in these patients [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%